Effects of roflumilast, a phosphodiesterase-4 inhibitor, on the lung functions in a saline lavage-induced model of acute lung injury - Kosutova, P; Mikolka, P; Kolomaznik, M; Rezakova, S; Calkovska, A; Mokra, D (Physiological research, 2017)
Acute lung injury (ALI) is associated with deterioration of alveolar-capillary lining and transmigration and activation of inflammatory cells. Whereas a selective phosphodiesterase-4 (PDE4) inhibitor roflumilast has exerted potent anti-inflammatory properties, this study evaluated if its intravenous delivery can influence inflammation, edema formation, and respiratory parameters in rabbits with a lavage-induced model of ALI. ALI was induced by repetitive saline lung lavage (30 ml/kg). Animals were divided into 3 groups: ALI without therapy (ALI), ALI treated with roflumilast i.v. (1 mg/kg; ALI+Rofl), and healthy ventilated controls (Control), and were ventilated for following 4 h. Respiratory parameters (blood gases, ventilatory pressures, lung compliance, oxygenation indexes etc.) were measured and calculated regularly. At the end of experiment, animals were overdosed by anesthetics. Total and differential counts of cells in bronchoalveolar lavage fluid (BAL) were estimated microscopically. Lung edema was expressed as wet/dry lung weight ratio. Treatment with roflumilast reduced leak of cells (P<0.01), particularly of neutrophils (P<0.001), into the lung, decreased lung edema formation (P<0.01), and improved respiratory parameters. Concluding, the results indicate a future potential of PDE4 inhibitors also in the therapy of ALI.
Keywords: Animals; Sodium Chloride; bronchoalveolární lavážní tekutina; Rabbits; Bronchoalveolar Lavage Fluid; Female; Lung; Administration, Intravenous; výsledek terapie; ženské pohlaví; Aminopyridines; intravenózní podání; chlorid sodný; inhibitory fosfodiesterasy 4; Phosphodiesterase 4 Inhibitors; Treatment Outcome; cyklopropany; bronchoalveolární laváž; Benzamides; Male; modely nemocí na zvířatech; benzamidy; Bronchoalveolar Lavage; Disease Models, Animal; plíce; Cyclopropanes; králíci; zvířata; mužské pohlaví; Acute Lung Injury; akutní poškození plic; aminopyridiny